Liquid‐Metal‐Templated Synthesis of 2D Graphitic Materials at Room Temperature. Issue 29 (8th June 2020) - Mayyas, Mohannad; Li, Hongzhe; Kumar, Priyank; Ghasemian, Mohammad B.; Yang, Jiong; Wang, Yifang; Lawes, Douglas J.; Han, Jialuo; Saborio, Maricruz G.; Tang, Jianbo; Jalili, Rouhollah; Lee, Sun Hwa; et al.
Abstract: Room‐temperature synthesis of 2D graphitic materials (2D‐GMs) remains an elusive aim, especially with electrochemical means. Here, it is shown that liquid metals render this possible as they offer catalytic activity and an ultrasmooth templating interface that promotes Frank–van der Merwe regime growth, while allowing facile exfoliation due to the absence of interfacial forces as a nonpolar liquid. The 2D‐GMs are formed at low onset potential and can be in situ doped depending on the choice of organic precursors and the electrochemical set‐up. The materials are tuned to exhibit porous or pinhole‐free morphologies and are engineered for their degree of oxidation and number of layers. The proposed liquid‐metal‐based room‐temperature electrochemical route can be expanded to many other 2D materials. Abstract : A liquid metal establishes an ultrasmooth liquid–liquid interface that catalyses the dissociation of organic precursors into interfacial graphitic carbon films. The electrochemical synthesis of these 2D graphitic films is accomplished at room temperature (with only a small energy input, an onset voltage of 0.45 V) and they self‐exfoliate from the nonpolar surface of the liquid metal by applying higher voltages.